The development of a tool to support the work of the Rehabilitation care worker in documenting information about rehabilitation and health needs among persons with disability in home and community setting - Hansen, Anthea (Division of Disability Studies, 2019)
The purpose of the study is to contribute to the development of a tool that can support the rehabilitation care worker towards intervention planning and the monitoring of their clients. The National Health Insurance and the Framework and Strategy for Disability and Rehabilitation of the South African Department of Health are strategies to work towards accessible, affordable, equitable and quality health care, which includes health promotion, disease prevention, curative, rehabilitation and palliative services for all South Africans. Both strategies emphasise the use of community health workers and mid-level workers as a key component of primary health care. In the Western Cape provincial Department of Health a new cadre, namely the rehabilitation care worker has been introduced as a member of the rehabilitation team. The introduction of the rehabilitation care worker is still in the pilot phase. The rehabilitation care workers face many barriers to providing effective care. One such challenge is the lack of a contextually relevant resource tool to collect information on the rehabilitation and health needs of persons with disabilities. The aim of the study was to develop a contextually relevant resource tool that would support the rehabilitation care worker in understanding and documenting how the rehabilitation and related health needs of persons with disabilities are met in home- and community-based settings. Three specific objectives were defined: i) to develop the content and domains of the rehabilitation and health information tool; ii) to establish the validity (face and content) of the rehabilitation and health information tool; and, iii) to test the application of the rehabilitation and health information tool on a sample of persons with disabilities. This study was an exploratory descriptive study adopting a sequential mixed methods design. There were two phases in this study. Phase 1 involved qualitative research methods in the development of the rehabilitation and health information tool through the use of document review and a focus group discussion with experts. Phase 2 of the study involved quantitative research methods in the field testing of the rehabilitation and health information tool by the rehabilitation care workers on a sample of persons with disabilities. The results of phase 1 included the development of the rehabilitation and health information tool, which was deemed by the experts to be a comprehensive, contextually relevant tool with face and content validity and could be easily administered by the rehabilitation care worker. The conceptual framework of the International Classification of Functioning, Disability and Health provided domains that could comprehensively document the multidimensional needs of persons with disabilities. The result was a draft rehabilitation and health information tool with 17 questions ranging across the domains of activities of daily living, sexual health, health behaviours, barriers and facilitators to good health, finance and understanding of disability. Changes were proposed to the wording, layout and flow of the tool and the persons with disabilities’ goals were included as an element . The inclusion of the end users as experts in the development resulted in a richer understanding needed for the shaping of this tool. The results of phase 2 highlighted that the rehabilitation and health information tool was able to describe the rehabilitation and health needs of persons with disabilities. Additionally the tool was able to document the specific goals of the persons with disabilities which is useful to plan and monitor intervention. The rehabilitation care workers reported the tool to be useful, easy to use, and provided a structured manner to collect information. They also reported that it was useful in stimulating conversations on sensitive topics. However, it was indicated that it took too long to complete and there were components that were incomplete. The rehabilitation and health information tool requires further refinement, validation and further follow-up testing before it can be formally adopted and implemented as part of the rehabilitation care worker’s standard practice.